2014
DOI: 10.1016/j.rie.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural subsidy policies fail to deal with child labour under agricultural dualism: What could be the alternative policies?

Abstract: Abstract:We provide a theoretical explanation why agricultural subsidy policies are likely to fail to ensure simultaneous eradication of the incidence of child labour and improvement in the well-being of the poor working families in terms of a three-sector general equilibrium model with child labour and agricultural dualism. We identify both demand and supply side effects of any policy intervention on child labour. We also suggest two alternative policies, a scheme of direct cash transfer to poor people and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…They have shown that higher economic growth may sufficiently raise the demand for commodities/services that use child labor thereby worsening the problem. For some other important explanations, see Chaudhuri and Dwibedi (), Gupta (), Jafarey and Lahiri (), Chaudhuri (, ) and Dwibedi and Chaudhuri (, ).…”
mentioning
confidence: 99%
“…They have shown that higher economic growth may sufficiently raise the demand for commodities/services that use child labor thereby worsening the problem. For some other important explanations, see Chaudhuri and Dwibedi (), Gupta (), Jafarey and Lahiri (), Chaudhuri (, ) and Dwibedi and Chaudhuri (, ).…”
mentioning
confidence: 99%
“…Child labour is primarily considered a poverty phenomenon (Basu, 2003; Dwibedi & Chaudhuri, 2014; Ersado, 2005; Frempong & Stadelmann, 2019). According to Basu and Van's (1998) luxury axiom, increasing income/wealth may reduce child labour incidence.…”
Section: Introductionmentioning
confidence: 99%
“…There are also works, e.g. Gupta (), Jafarey and Lahiri (), Chaudhuri (), Chaudhuri and Gupta (), Chaudhuri and Dwibedi (, ), and Dwibedi and Chaudhuri (, ), that have examined the consequences of trade sanctions, education subsidy and mid‐day meal programs and different liberalized economic policies on the incidence of child labor in the developing economies using different general equilibrium structures. However, none of these works has made any attempt to study the effects of different trade and domestic policies on the sectoral allocation of child labor and explain the atypical empirical finding that the use of child labor as domestic help has been on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in a country such as India where corruption is rampant, benefits of different subsidies hardly reach the target group(s). Of late, India has started implementing direct cash transfer for some of its subsidy programs to the bank accounts of the target groups through the “Aadhaar scheme.” The consequence of such a direct cash transfer scheme on child labor has been analyzed in Dwibedi and Chaudhuri ().…”
mentioning
confidence: 99%
See 1 more Smart Citation